Implementing Sustainable Development Goal on Education (SDG4) amid Donor Fatigue: Challenges for the Global South - Kakupa, Paul; Shayo, Happy Joseph (Advances in Social Sciences Research Journal, 2021)
This paper critically reflects on the implementation of the Sustainable Development Goal on education (SDG4) in the Global South amid apparent donor fatigue. It also highlights international observers’ concerns about a huge funding gap in the implementation of SDG4 in the Global South. With the COVID-19 pandemic currently ravaging the world, this funding gap will only widen. In the face of these challenges, low-income countries with a high dependency on aid remain at risk of defaulting on most SDG4 targets. While reflecting on what the decline in education aid might mean for low-income countries, the paper argues that a truly transformative approach can help these countries achieve SDG4 and its sustainability agenda despite funding challenges.